2023
DOI: 10.15421/012302
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics and spatial distribution of large carnivores in the Ukrainian Carpathians and Polissya

Abstract: Large carnivores play an important role as indicators of the state of the natural ecosystems. The analysis of the number and distribution of large carnivores (brown bear – Ursos arctos, Eurasian lynx – Lynx lynx and grey wolf – Canis lupus) was established in the Ukrainian Carpathians and Ukrainian Polissya. Annual data on the number of large carnivores on the territories of hunting units and nature conservation areas from 2009 to 2019 was summarized. To analyze the number and distribution of large carnivores … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Although concrete distribution and connectivity maps are still missing, building on work by Cherepanyn et al. (2023), we add another piece of optimistic evidence concerning the reportedly negative lynx status in the Ukrainian Carpathians noted by the (Bonn Lynx Expert Group, 2021).…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…Although concrete distribution and connectivity maps are still missing, building on work by Cherepanyn et al. (2023), we add another piece of optimistic evidence concerning the reportedly negative lynx status in the Ukrainian Carpathians noted by the (Bonn Lynx Expert Group, 2021).…”
Section: Discussionmentioning
confidence: 78%
“…The need for harmonised, scientific monitoring of Eurasian lynx is well established (Boitani et al., 2015; Bonn Lynx Expert Group, 2021), and there are huge opportunities to enhance assessments of lynx status where data gaps exist (Kubala et al., 2021). For example, gathering data collected outside of research and in Ukrainian language, as demonstrated in (Cherepanyn et al., 2023). Ukraine is also a candidate member for the EU, and a future ascension would presumably invoke standardised reporting of lynx monitoring under the Habitats Directive (EC, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations